Machine Learning in Structural Design: An Opinionated Review - Málaga-Chuquitaype, Christian (Frontiers in Built Environment, 2022)
The prominence gained by Artificial Intelligence (AI) over all aspects of human activity today cannot be overstated. This technology is no newcomer to structural engineering, with logic-based AI systems used to carry out design explorations as early as the 1980's. Nevertheless, the advent of low-cost data collection and processing capabilities have imprinted new impetus and a degree of ubiquity to AI-based engineering solutions. This review paper ends by posing the question of how long will the human engineer be needed in structural design. However, the paper does not aim to address this question, not least because all such predictions have a history of going wrong. Instead, the paper assumes throughout as valid the claim that the need for human engineers in conventional design practice has its days numbered. In order to build the case towards the final question, the paper starts with a general description of the AI frameworks currently available and their Machine Learning (ML) sub-classes. The paper then proceeds to review a selected number of studies on the application of AI in structural engineering design. A discussion of specific challenges and future needs is presented with emphasis on the much exalted roles of 'engineering intuition' and 'creativity'. Finally, the conclusion section of the paper compiles the findings and outlines the challenges and future research directions.